Grounded Theory of Istighfar and Sholawat Management as Non-Medical Intervention for Santri Patients with Chronic Diseases in Nganjuk - M. Munir (Pascasarjana Manajemen Pendidikan Islam STAI Darussalam Nganjuk, Indonesia, 2026)
Background: Chronic diseases among santri (Islamic boarding school students) in Nganjuk pose physical and psychological challenges. Non-medical interventions based on Islamic spiritual practices such as istighfar (seeking forgiveness) and sholawat (praising the Prophet) are commonly used but lack theoretical grounding. Objective: This study aims to develop a grounded theory of istighfar and sholawat management as a non-medical intervention for santri with chronic illnesses. Method: A qualitative grounded theory approach was employed. Data were collected through in-depth interviews, participant observation, and document analysis involving 15 santri with chronic diseases, caregivers, and religious teachers in three Islamic boarding schools in Nganjuk. Data analysis followed Corbin and Strauss’s grounded theory procedure. Findings: The core category identified is “spiritual-emotional regulation through istighfar and sholawat,” consisting of four main processes: (1) awareness of illness as a spiritual signal, (2) structured practice of istighfar and sholawat, (3) perceived psychospiritual relief, and (4) transformation of coping mechanisms. Conclusion: Istighfar and sholawat function as a non-medical intervention that enhances resilience and spiritual acceptance. A substantive theory is proposed for integration into holistic care for santri with chronic conditions.